Avaliação in vitro do extrato salino bruto das folhas de prosopis juliflora sobre oviposição em fêmeas de rhipicephalus sanguineus (LATREILLE, 1806) (ACARI: IXODIDAE) - Medeiros Neta, Madalena Dantas de (Universidade Federal Rural do Semi-Árido, 2019)
Rhipicephalus sanguineus, popularly known as brown dog tick, has worldwide distribution, with an emphasis on higher temperature locations. It is controlled by acaricides that can cause side effects and parasitic chemical resistance, which enabled research for control alternatives, such as herbal medicines. In this context, the present study aimed to evaluate in vitro parasiticidal effect of Prosopis juliflora crude saline extract on oviposition of R. sanguineus females. The leaves were dried, crushed and subjected to extraction in sodium chloride solution to prepare the extract. While engorged teleogines were collected from dogs without antiparasitic use for at least 30 days. These females were homogenized (by weight) in groups, then immersed in 20 mL of the extract, and subjected to two exposure times (10 and 20 minutes). For the negative control distilled water was used and for the positive commercial acaricide (Amitraz). After the proposed times, they were fixed in Petri dishes and taken to the incubator oven, where they all presented oviposition, except for the positive control. As a result, an egg laying index of 45% was obtained in both the negative control group and the experimental groups, thus not showing a decrease in female oviposture.
Monografia
Keywords: Algaroba; Carrapato; Fitoterápico; Algaroba; Tick; Herbal medicine; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA